Analisis Yuridis Tindak Pidana Pemerasan dengan Pengancaman (Studi Putusan Pengadilan Negeri Medan Nomor 1625/Pid.B/2024/PN.Mdn) - Haikal Arba’a (Albayan Journal of Islam and Muslim Societies, 2024)
This study analyzes the legal aspects of extortion accompanied by threats as regulated under Article 368 of the Indonesian Criminal Code, using a case study of Decision No. 1625/Pid.B/2024/PN.Mdn. Employing a normative juridical approach combined with qualitative analysis, the research examines the elements of the criminal act, the evidentiary process, and the judge’s legal considerations. Findings show that the defendant’s actions fulfilled all material and formal elements of extortion by threat. However, discrepancies remain between the theoretical interpretation of coercion and its judicial application. Therefore, the research suggests the need for consistency in sentencing and preventive measures through public legal awareness.